ANALISIS PEMAHAMAN MAHASISWA AKUNTANSI TERHADAP KONSEP ASET, KEWAJIBAN, DAN EKUITAS - BUDI HARTONO KUSUMA; NURAINUN BANGUN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2011)
The study examined the differences of understanding assets, liabilities, and equities concepts among college students majoring in accounting with different educational background. Data were collected by questionnaires distribution to 122 college students majoring in accounting as respondents. One hundred and seven of 122 questionnaires were processing using the Kruskal Wallis H test. The results of this study showed that there are no differences of understanding assets, liabilities, and equities concepts among college students majoring in accounting. Different educational background did not result the differences of understanding assets, liabilities, and equities concepts.